Manure Waste Management to Produce and Utilize Biogas Efficiently and Effectively in a Smart Eco-Social Village in Bandung - Tan-Soetedjo, Jenny Novianti Muliarahayu; Ramadhany, Putri; Prasetyo, Susiana (AIBPM Publisher, 2022)
The river is one of the primary sources of fresh water. It serves purposes for irrigation systems in agriculture, fulfilling domestic needs (water drinking, washing), transportation medium, energy production, and leisure. In West Bandung, the Cikapundung River becomes the source of life to sustain the population. More than 50% of the population upstream Cikapundung lives as agriculture and dairy farmers. Unfortunately, due to those activities, the river condition is considered unhealthy. Agriculture and dairy farmers discharge their wastes into the river instead of employing them for biogas, despite biogas's role in ensuring farming sustainability. Thus, Chemical Engineering Department and Student Society (HMPSTK) of Parahyangan Catholic University (UNPAR) constructed a system involving biodigester to produce biogas from agricultural waste (cow manure and organic waste) as a prototype solution for this issue. The community service program was divided into seven stages: a) Problem identification, b) Location survey and advocacy, c) Sample collection, d) Research, e) Construction of a biogas digester, f) Socialization with the local community, and g) Follow-up of the outcomes. In fact, a 5,000 Liter of fiberglass bio-digester was successfully installed in Cibodas Village, Maribaya, Lembang, with the help of PRIMARY (Program Biogas Rumah), a local biogas contractor. The mixture of livestock manures and organic waste of a 3:1 ratio produced the largest biogas volume. Biogas generated from biodigester was applied for cooking and lighting kerosene lamps. The result showed that no leakage was observed until 3-years of installation of the biodigester. However, it is suggested that a continuous and solid system involving multiple ways of manure processing such as the biogas and vermicompost production as well as the biogas utilization should be designed to encourage not only a eco-friendly solution but also to initiate a circular economy model in the community. Thus, it will be a sustainable solution not only for overcoming the largest issue of Cikapundung Rivers's organic waste disposal but also for the other agriculture and farming in Indonesia.